What Drives Built‐Up Area Expansion on Islands? Using Soil Sealing Indicators to Estimate Built‐Up Area Patterns on Aegean Islands, Greece. (27th February 2017) - Kizos, Thanasis; Tsilimigkas, Georgios; Karampela, Sofia
Abstract: The dispersion of built‐up areas in peri‐urban zones is considered an important, almost irreversible environmental threat, especially in coastal zones and islands. In this paper, we use soil sealing datasets derived from the European Environment Agency in order to estimate the expansion of built‐up areas in the North and South Aegean islands in Greece. We examine these differences in relation to socio‐economic features of the islands, especially tourism development, second home development and size and geographical position of the islands. The findings show divergent levels of soil sealing and a variety of spatial configurations, such as scattered growth of built‐up land in coastal areas and peri‐urban growth in rural areas. Higher cover of the total area of islands by sealed soil is related to tourism, but it seems that second homes are also an important driver, especially for smaller islands located relatively close to Athens. From a planning and management perspective, these findings can assist local or regional administration to assess the effectiveness of land use management plans and manage flows and processes.